2014
DOI: 10.1155/2014/378651
|View full text |Cite
|
Sign up to set email alerts
|

Intrastrain Comparison of the Chemical Composition and Antioxidant Activity of an Edible Mushroom,Pleurotus giganteus, and Its Potent Neuritogenic Properties

Abstract: Two strains of Pleurotus giganteus (commercial and wild) were tested for their ability to induce neurite outgrowth in rat pheochromocytoma (PC12) and mouse neuroblastoma-2a (N2a) cells. Treatment with the mushroom extracts resulted in neuronal differentiation and neuronal elongation, but not nerve growth factor (NGF) production. Linoleic acid (4.5–5.0%, w/w) which is a major fatty acid present in the ethanol extract promoted NGF biosynthesis when augmented with low concentration of NGF (5 ng/mL). The two strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 46 publications
2
16
0
2
Order By: Relevance
“…Therefore, it is pertinent to suggest that EPG exerts its anti-inflammatory activity by suppressing JAK2-STAT pathway. Phan reported that P.giganteus has high glycine (non-essential amino acid) content which acts on inflammatory cells to suppress activation of transcription factors and the formation of free radicals and inflammatory cytokine [26, 27]. Hence, this could cause the reduction of inflammatory mediators by EPG as mentioned above.
Fig.
…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is pertinent to suggest that EPG exerts its anti-inflammatory activity by suppressing JAK2-STAT pathway. Phan reported that P.giganteus has high glycine (non-essential amino acid) content which acts on inflammatory cells to suppress activation of transcription factors and the formation of free radicals and inflammatory cytokine [26, 27]. Hence, this could cause the reduction of inflammatory mediators by EPG as mentioned above.
Fig.
…”
Section: Results and Discussionmentioning
confidence: 99%
“…8). According to Phan, P. giganteus is a mushroom that has high phenolic content which positively correlates with its antioxidant activity (free radical scavenging and ferric reducing power) [26]. Lai also reported that the phenolic compounds from the pigeon pea ( Cajanus cajan L.) correlates with the high antioxidant activity and possess anti-inflmmatory effect as well [35].…”
Section: Results and Discussionmentioning
confidence: 99%
“…These changes may also be due to the ~22.10% higher protein concentration in P. citrinopileatus than in other Pleurotus spp. (Musieba et al, 2013;Phan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The present findings suggest that changes could occur to elicit a positive effect on reproduction in fruit flies fed with PAM, whereas these same benefits are not clear when used PSC supplement. Both mushroom species are reported in the literature as being highly nutritious, presenting antioxidant and scavenging effects when consumed (Musieba et al, 2013;Phan et al, 2014). However, the lack of studies evaluating the effects of these mushrooms experimentally in animal models, much less their effects on fertility and fitness, prevents us from making major assumptions about the results.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological manipulation of cellular stress pathways is emerging as a viable approach to treating certain neurologic diseases, such as Alzheimer's disease and psychiatric disorders, such as schizophrenia 51 . Specifically, small redox active molecules, such as the phytochemicals sulforaphane and hydroxytyrosol, or nutritional mushrooms may be potential candidates to modulate physiological pathways associated with cellular stress response and vitagene networks 52 56 and synaptic dysfunction 57 . Conceivably, such therapeutic tactics may be of value in mitigating or perhaps preventing signs and symptoms of neurodegeneration.…”
Section: Redox Homeostasismentioning
confidence: 99%